PRIVATE ISSUES IN PESAT IN LATE COLONIAL JAVA (Paramita: Historical Studies Journal, 2012)
Pesat was a local newspaper in Semarang published in the 1940s during the late colonial era. The establishment of Pesat could not be separated from the couple of I.M. Sajoeti and S.K. Trimurti, the owners of the newspaper, who were best-known as activitists of Political Party and senior journalists in Semarang at that time. As a local newspaper, the content of this publication differed considerably from the other local newspaper which mostly focused on news and advertisements. Pesat continuously published some information that had not been addressed by the media anywhere before. Pesat published transparently on the problems of family life and household. In particular, Pesat pointed the problems of marriage which placed women in domestic area in which they were not permitted to speak about the problems they were facing to other people in the public domain. This meant that a matter concerning the life of household which was previously considered private space was now published as news available to newspaper readers. Keywords: Pesat, private, colonial, Semarang, Java. Â  Pesat adalah sebuah koran lokal di Semarang yang diterbitkan pada 1940-an selama era kolonial akhir. Pembentukan Pesat tak lepas dari pasangan IM Sajoeti dan SK Trimurti, pemilik surat kabar, yang dikenal sebagai aktifis Partai Politik dan wartawan senior di Semarang pada waktu itu. Sebagai koran lokal, isi dari publikasi ini berbeda jauh dari koran lokal lainnya yang berfokus pada berita dan iklan. Pesat terus menerbitkan beberapa informasi yang belum ditangani oleh media manapun sebelumnya. Dalam publikasi mereka, Pesat dipublikasikan secara transparan pada kehidupan masalah keluarga dalam rumah tangga. Secara khusus, diangkat masalah seputar pernikahan yang menempatkan perempuan dalam ruang domestik dan perempuan tidak diperbolehkan untuk berbicara tentang masalah yang mereka hadapi kepada orang lain dalam domain publik. Ini berarti bahwa masalah yang berkenaan dengan kehidupan rumah tangga yang sebelumnya dianggap ruang pribadi yang ada di luar keluarga diizinkan untuk tahu tentang itu sekarang telah diterbitkan sebagai berita tersedia bagi pembaca surat kabar. Kata kunci: Pesat, pribadi, kolonial, Semarang, Jawa. Â